Conceptual Principles for Forming a System of Economic Support for Ukraine’s Armed Defense in the Context of Hybrid Warfare - Polovenko, Vitalii (Social Development and Security, 2025)
Purpose: Development of the conceptual foundations for establishing an effective system of economic support for Ukraine’s armed defense in the context of hybrid warfare. Method: analysis, synthesis. Findings: A holistic approach to developing a system of economic support for the armed defense of Ukraine in the context of hybrid warfare has been developed. A system based on four key elements has been proposed: defense financing, logistical support, innovation development, and resource management. The principles of prioritization, flexibility, transparency, and integration, which ensure the system’s adaptability to the dynamic conditions of hybrid warfare, have been defined. A comprehensive model of economic support, which serves as a tool for enhancing defense capabilities, has been created. Key approaches to building an effective system of economic support that takes into account current challenges and Ukraine’s experience in countering hybrid aggression (diversification of funding sources, digitalization of resource management, development of the defense industry, and countering economic threats) have been proposed. Theoretical implications: The research expands the theoretical understanding of the system of economic support for the armed defense of the state in the context of hybrid warfare. The proposed approaches and principles can be used for further theoretical developments in the field of defense economics and national security. The model of economic support for armed defense can serve as a basis for developing other models and concepts in conditions of uncertainty. Practical implications: The research results are significant for improving Ukraine’s defense policy, in particular in the development of financing strategies, modernization of logistics systems, implementation of innovative technologies, and strengthening cybersecurity. The proposed model can be used for practical implementation at various levels of defense management in the country. The implementation of the model involves the creation of digital platforms for monitoring, the development of the defense industry, and the strengthening of international cooperation. The research results can be used for training and professional development of specialists in the field of defense economics and national security. Successful implementation of the research results will contribute to increasing the defense capability and economic stability of Ukraine in the context of hybrid warfare. Paper type: theoretical.